2008
DOI: 10.1097/01.nmc.0000341257.26169.30
|View full text |Cite
|
Sign up to set email alerts
|

New Mothers' Views of Weight and Exercise

Abstract: Purpose-To describe the attitudes and preferences of ethnically diverse new mothers on weight and exercise of women like them.Study Design and Methods-Exploratory, qualitative study. Forty-nine ethnically diverse women were interviewed during the first year following childbirth regarding beliefs about weight, choices of exercise, walking for exercise, perceived benefits, barriers, and facilitators of exercise. Content analysis techniques were used to analyze the data.Results-Weight was a significant concern fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 16 publications
4
59
1
Order By: Relevance
“…However, neither of these studies focused on new firsttime mothers. As the most common inflection point for women becoming overweight has been their first live birth (Davis et al, 2009), weight management interventions need to be focused on new first-time mothers (Groth & David, 2008). Our findings support the idea that reducing maternal stress is key to facilitating maternal PA and further suggest that an intervention to facilitate weight loss should directly address parenting stress in new mothers, in addition to nutrition and PA.…”
Section: Discussionsupporting
confidence: 68%
“…However, neither of these studies focused on new firsttime mothers. As the most common inflection point for women becoming overweight has been their first live birth (Davis et al, 2009), weight management interventions need to be focused on new first-time mothers (Groth & David, 2008). Our findings support the idea that reducing maternal stress is key to facilitating maternal PA and further suggest that an intervention to facilitate weight loss should directly address parenting stress in new mothers, in addition to nutrition and PA.…”
Section: Discussionsupporting
confidence: 68%
“…Fatigue is a reasonable concern, given sleep issues, 46 and physical activity may help return feelings of energy. 12,43 Health issues were reported less often than expected. At 3 months postpartum, only 5% of women reported being physically ill or unable (including medical limitations or depression), and 3% reported nursing issues.…”
Section: Barriers and Enablers To Physical Activitymentioning
confidence: 75%
“…Several studies have noted lack of time as a barrier to physical activity postpartum. [41][42][43] Child care issues have also been reported, 43 and in one study, those who reported child care as a barrier were more likely to be insufficiently active at 6 months postpartum. 15 Encouraging walking, with the baby in the stroller, may be one way to overcome this barrier and may be a promising transitional activity.…”
Section: Barriers and Enablers To Physical Activitymentioning
confidence: 95%
“…Cultural and social value placed on ideal weight also influences 38 body image perceptions. White and Hispanic women place a higher value on being at a healthy 39 weight than do Black women (Groth & David, 2008), and postpartum women of high 40 socioeconomic status selected a thinner figure as their desired figure than did women of medium 41 and low socioeconomic status (Shrewsbury et al, 2008). 42…”
Section: Provided Evidence 28mentioning
confidence: 99%